Connectivity between mPFC and PCC predicts post‐choice attitude change: The self‐referential processing hypothesis of choice justification - Tompson, Steven (Hum Brain Mapp, 2016)
Prior research shows that after making a choice, decision makers shift their attitudes in a choice‐congruous direction. Although this post‐choice attitude change effect is robust, the neural mechanisms underlying it are poorly understood. Here, we tested the hypothesis that decision makers elaborate on their choice in reference to self‐knowledge to justify the choice they have made. This self‐referential processing of the choice is thought to play a pivotal role in the post‐choice attitude change. Twenty‐four young American adults made a series of choices. They also rated their attitudes toward the choice options before and after the choices. In support of the current hypothesis, we found that changes in functional connectivity between two putative self‐regions (medial prefrontal cortex and posterior cingulate cortex/precuneus]) during the post‐choice (vs. pre‐choice) rating of the chosen options predicted the post‐choice shift of the attitudes toward the chosen options. This finding is the first to suggest that cognitive integration of various self‐relevant cognitions is instrumental in fostering post‐choice attitude change. Hum Brain Mapp 37:3810–3820, 2016. © 2016 Wiley Periodicals, Inc.